2018
DOI: 10.1016/j.jml.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The list strength effect in source memory: Data and a global matching model

Abstract: A critical constraint on models of item recognition comes from the list strength paradigm, in which a proportion of items are strengthened to observe the effect on the non-strengthened items. In item recognition, it has been widely established that increasing list strength does not impair performance, in that performance of a set of items is unaffected by the strength of the other items on the list. However, to date the effects of list strength manipulations have not been measured in the source memory task. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 83 publications
6
42
2
Order By: Relevance
“…In its standard form, the Osth and Dennis (2015) model does not account for prior lists that are part of the same experiment. Regardless, the conclusions of Osth and Dennis (2015) were reinforced when the model was expanded to account for source memory data (Osth, Fox, McKague, Heathcote & Dennis, 2018), and when the model was integrated with the diffusion decision model (DDM; Ratcliff, 1978) to account for response times (RTs) and various effects (e.g., LLE, test position effect) simultaneously (Osth, Jansson et al, 2018).…”
Section: Evidence Against the Item-noise Account Of Memorymentioning
confidence: 99%
“…In its standard form, the Osth and Dennis (2015) model does not account for prior lists that are part of the same experiment. Regardless, the conclusions of Osth and Dennis (2015) were reinforced when the model was expanded to account for source memory data (Osth, Fox, McKague, Heathcote & Dennis, 2018), and when the model was integrated with the diffusion decision model (DDM; Ratcliff, 1978) to account for response times (RTs) and various effects (e.g., LLE, test position effect) simultaneously (Osth, Jansson et al, 2018).…”
Section: Evidence Against the Item-noise Account Of Memorymentioning
confidence: 99%
“…The null list-strength effect has been replicated numerous times across different memory labs (Kahana, Rizzuto, & Schneider, 2005;Murnane & Shiffrin, 1991a, 1991bRatcliff, McKoon, & Tindall, 1994;Ratcliff et al, 1992;Yonelinas, Hockley, & Murdock, 1992). It has even been found in other memory tasks, such as associative recognition , cued recall (Wilson & Criss, 2017), and source memory (Osth, Fox, McKague, Heathcote, & Dennis, 2018). A mathematical analysis by Shiffrin, Ratcliff, and of the existing memory models found that none of the models at the time yielded the correct predictions about the list-strength paradigm.…”
Section: Challenges To Global Matching Modelsmentioning
confidence: 95%
“…Item noise exerted only a negligible influence on words and natural scenes, while there were larger influences for visually confusable stimuli such as faces and fractal images. Moreover, in recent years the model was extended to complete RT distributions (Osth, Jansson, et al, 2018) and to source memory (Osth, Fox, et al, 2018) -the introductions of each of these constraints did not change the original conclusions, reinforcing the idea that forgetting in recognition memory is caused by memories acquired prior to the list episode.…”
Section: Sources Of Interference In Recognition Memorymentioning
confidence: 97%
“…Fox et al (2019) replicated the findings of Brandt et al (2019) with word stimuli and modeled the increase in interference in lists across a session using the Osth and Dennis model, which is a global matching model that is able to decompose performance into the contributions of item-noise and noise from pre-experimental sources, namely context-noise and background-noise. Previous investigations using the model have found a dominance of pre-experimental interference in recognition memory (Osth & Dennis, 2015;Osth, Fox, McKague, Heathcote, & Dennis, 2018;Osth, Jansson, et al, 2018). However, none of these investigations considered the buildup of interference within a session, meaning there was no distinction made between short lists that were tested first (which are advantaged over long lists) or short lists that were tested after long lists (which perform comparably to longer lists).…”
Section: Implications For Item Noise and Context Noise Modelsmentioning
confidence: 99%